Effective Communication Strategies between Teachers and Parents through a Collaborative Approach to Improve Student Achievement in Primary Schools - Maman Rachman; Saeful Muslim; Dendi Suparman; Efrita Norman (Jurnal Dirosah Islamiyah, 2024)
This study investigates effective communication strategies between teachers and parents through a collaborative approach to improve students' academic achievement in primary schools. The background highlights that teacher-parent collaboration plays a vital role in shaping students' academic success, especially during the primary education stage. The purpose of the study is to identify the most effective strategies for building collaborative communication between teachers and parents to enhance student performance. Using a systematic literature review (SLR) methodology, the research synthesizes findings from studies published between 2019 and 2024. The review followed the PRISMA framework to systematically select and analyze relevant studies on communication strategies and their impact on student achievement. The results reveal that structured, transparent communication, particularly supported by technology, significantly enhances teacher-parent collaboration, leading to improved student motivation and academic outcomes. The study concludes that utilizing digital platforms for communication bridges the gap between teachers and parents, enabling more efficient and sustained interaction. These findings contribute to the field by offering practical guidelines for primary schools to optimize parental involvement through collaborative communication strategies. Although the research is comprehensive, further empirical studies are required to explore its application in diverse cultural and socioeconomic contexts.